2006
DOI: 10.1111/j.1399-3038.2005.00359.x
|View full text |Cite
|
Sign up to set email alerts
|

Basophil Activation Test and specific IgE measurements using a panel of recombinant natural rubber latex allergens to determine the latex allergen sensitization profile in children

Abstract: There are no documented studies that describe natural rubber latex (NRL) sensitization in children with a history of surgical intervention but without any congenital malformation (urogenital anomalies, spina bifida, etc.), although some authors have studied NRL allergy in children without a history of surgical intervention. The aim of this work was to evaluate the sensitization profile to single NRL allergens in children without spina bifida and without repeated surgical interventions, by using different recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
8

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 42 publications
2
20
0
8
Order By: Relevance
“…The stimulatory effect of the extracted latex allergens could be demonstrated by activation of basophils from sensitised workers as previously demonstrated in other settings [23]. Data from other studies on latex exposure have demonstrated that latex allergen levels above 1 µg/g of glove are potentially sensitising [24], confirming the elevated health risk of the workers exposed to the processed elastics in the investigated factory.…”
Section: Discussionsupporting
confidence: 63%
“…The stimulatory effect of the extracted latex allergens could be demonstrated by activation of basophils from sensitised workers as previously demonstrated in other settings [23]. Data from other studies on latex exposure have demonstrated that latex allergen levels above 1 µg/g of glove are potentially sensitising [24], confirming the elevated health risk of the workers exposed to the processed elastics in the investigated factory.…”
Section: Discussionsupporting
confidence: 63%
“…In several validated studies [57,58,59,60,61,62,63] (table 3), BAT was shown to demonstrate a sensitivity and specificity for CD63 expression of >90%, with one exception in which sensitivity was reported to be 75% for CD203c and 50% for the CD63 assay [60]. BAT is the test which reflects the most closely clinical provocation.…”
Section: Clinical Indications Of Batmentioning
confidence: 99%
“…Many of these studies have been reviewed recently [8,9,10]. Herewith, tables 1, 2, 3, 4, 5, 6, 7summarize the results of validated clinical studies performed with various allergens such as inhalant allergens [25,26,27,28,29,30,31,32,33] (table 1), hymenoptera venoms [34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56] (table 2), latex [57,58,59,60,61,62,63] (table 3), food [64,65,66,67,68,69,70,71,72,73,74,75,76,77,78,79,80] (table 4) and drugs [81,82,83,84,85,86,87,88,89,90,91,92,93,94,95,96,97,98,99,100,101,…”
Section: Clinical Issues In the Diagnostic Use Of Batmentioning
confidence: 99%
“…En las que emplearon IgE específica fue la presencia de concentraciones mayores a 0,35UIL y en los que emplearon como estándar de referencia el diagnóstico clínico se evaluó la En la tabla 2 se presenta la descripción de los valores para la evaluación diagnós-tica, sumado al porcentaje del peso que presenta cada estudio individual en el valor global del CP+, el CP-y la ORD. En esta se observó que el estudio de Sturm et al 20 con alergeno de avispas presentó el mayor peso en los resultados del CP+, mientras que para el CP-fue el de Sanz M et al 19 (tabla 2).…”
Section: Resultsunclassified